The Relevance Of The Seven Premises Discussed By Fullan’s Change Theory In Higher Education In Malaysia - Cheong, Kar Mee; Hussin, Hanipah; Nair, R. Sudha; Noordin, Noorzareith Sofeia; Abdul Kadir, Noriati; Jusoh, Zainuddin (Medwell Journals, 2016)
This is a review study related to seven core premises discussed by Fullan in Department of Languages, Centre of Languages and Human Development, Universiti Teknikal Malaysia Melaka (UTeM). Those premises are a focus on motivation capacity building with a focus on results; learning in context; changing context; a bias for reflective action; tri-level engagement and persistence and flexibility in staying the course. This study provides a picture for a real scenario which stresses change theory is important in driving education reform. The literature survey shows it is significant to the current scenario happened in UTeM. The suggestion is all the stakeholders need to take up challenges in ensuring the successful education system reform in the higher learning institution for the long term sustainability development goals.